Escravos japoneses, chineses e coreanos nas redes mercantis portuguesas (séculos XVI e XVII) - Faria, Patricia Souza de (Afro-Ásia, 2021)
Resenha de: SOUSA, Lúcio de. The Portuguese Slave Trade in Early Modern Japan: Merchants, Jesuits, and Japanese, Chinese, and Korean Slaves. Leiden: Brill, 2019. 594 p.